ЎҚУВЧИЛАРНИ КАСБ-ҲУНАРГА МАҚСАДЛИ ЙЎНАЛТИРИШ МЕХАНИЗМЛАРИ (“Мўйноқ” кичик саноат зонаси мисолида) - Хайдаров, О. (SCIENCE and SOCIETY, 2017)
The article deals with the mechanism of professional orientation of learners in regions, according to conditions of their perspective development on the basis of state programme of the regional development of the country.
Keywords: zone of chemical industry zone; labour rescources; prosperous indexes; aim directed professions; investment; enterprise subjects; employment